Regarding The Chemical Abstracts Centennial (Winter 2007) - Janice Mears (Issues in Science and Technology Librarianship)
A letter to the editor is presented in response to the article "The Chemical Abstracts Centennial: Whither CAS?" in the winter 2007 issue.